THE SELF AND THE OTHER IN LEVINAS AND SPINOZA - Adams, Don (Journal of Dharma, 2018)
Emmanuel Levinas in his ethics elucidates his key concept of the other-directed self by opposing it to the wholly self-interested self, as he interprets it, in the ethics of Baruch Spinoza. However, when we consider the Spinozan self within the context of his own ethical system, we find that it also ultimately is other-directed, but in a manner quite distinct from that of the Levinasian self. The contrasting ethical selves of Levinas and Spinoza provide alternative models of existing ethically in the world, both of which are in insistent opposition to the modern humanist valorization of the autonomous egoistic individual as a valid ontological concept and worthwhile ethical ideal.